Biomaterials from nature for advanced devices and therapies - Neves, N. M. (2016)
The book provides in-depth information on natural biomaterials and their applications for translational medicine, covering topics such as tissue engineering with collagens or gelatines and natural materials for protein purification and drug delivery. Edited by world-leading experts with contributions from top-notch international scientists, it collates the experience and cutting-edge knowledge on natural biomaterials from all over the world, making the book a must-have publication on the shelf of every biomaterials lab.